1994
DOI: 10.1177/0741088394011003002
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Written Between-Draft Responses on Students' Writing and Reasoning about Literature

Abstract: Although studies of writing and literary understanding have demonstrated the value of analytic essay writing for enhancing story understanding, these studies have focused on student's initial interpretations without considering the effects of a teacher's support and direction. The purpose of this study was to explore how 9th- (n = 6) and 11th- (n = 6) grade students reformulated and extended their initial written analyses of two short stories through revisions fostered by two different kinds of between-draft w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
0
10
0
1
Order By: Relevance
“…To examine how the two instructional conditions affected students' later responses to the story, students in each of the classes responded to three questions concerning the story. These questions were designed to elicit paragraph-length answers at each of three levels of understanding: description, interpretation, and generalization (Marshall, 1987;Newell, 1994). At the descriptive level, students were asked to recall the literal features of the text itself: "Describe the relationship between Amy and her two children."…”
Section: Flwji Newellmentioning
confidence: 99%
See 1 more Smart Citation
“…To examine how the two instructional conditions affected students' later responses to the story, students in each of the classes responded to three questions concerning the story. These questions were designed to elicit paragraph-length answers at each of three levels of understanding: description, interpretation, and generalization (Marshall, 1987;Newell, 1994). At the descriptive level, students were asked to recall the literal features of the text itself: "Describe the relationship between Amy and her two children."…”
Section: Flwji Newellmentioning
confidence: 99%
“…For this analysis, a factorial design with multiple measures was employed with instructional task (reader-based vs. teacher-centered) and mode of literary response (description, interpretation, and generalization) as betweensubject factors. The dependent measures included scores for the quality of written response to the three questions at each level of story understanding: description, interpretation, and generalization (Marshall, 1987;Newell, 1994).…”
Section: Instructional Tasks F\mt\mentioning
confidence: 99%
“…Authentic questioning (Goldschmidt, 2010) supports students in addressing interpretive dilemmas and interrogating issues they find compelling (Fecho, 2011). Whereas directive comments lead students to defer to the teacher's knowledge, questioning enhances students' own comprehension (Newell, 1994). Questioning feedback allows teachers to demonstrate self-assessment and problem-solving strategies (Zimmerman & Kitsantas, 2002).…”
Section: Joelle Pedersenmentioning
confidence: 99%
“…The inclusion of writing assignments as a means of developing narrative understanding is critical. A number of studies have demonstrated that written responses aimed at acquiring a holistic understanding of narratives may have a significant impact on students' literary responses (Marshall, 1987;Newell, 1994;Wong et al, 2002). In a meta-analysis of nine experiments in which students wrote extended interpretive responses to text, Graham and Hebert (2010) found an average effect size of 0.77 on students' reading comprehension.…”
Section: Strategy Instruction In the Dialogic Approachmentioning
confidence: 99%
“…This research rests on the assumption that the type of dialogic interaction in both speech and writing that is associated with greater improvement in narrative reading performance (Applebee et al, 2003;Nystrand et al, 1997;Newell, 1994;Wong, Kuperis, Jamieson, Keller, & Cull-Hewitt, 2002) may be combined with strategy instruction in order to form a broad, supportive environment for developing complex narrative comprehension. In this study, the instructional design is primarily based on theory of cognition and metacognition, with an emphasis on the mapping of learning processes from the perspective of comprehension strategies (Graesser, 2007;Griffith & Ruan, 2005).…”
Section: Strategy Instruction In the Dialogic Approachmentioning
confidence: 99%